Tree diversity and structure in carbonate calcium banks in Calakmul, Mexico - Esparza-Olguín, Ligia (2021)
Introduction: Tree vegetation of forests that develops in karst environments dominated by calcium carbonate faces the restriction of water and nutrients, which negatively affects its development. Objective: Analyze the composition, diversity, and structure of tree vegetation that develops in calcium outcrops (yesales) and their edaphic conditions compared to those present in the adjacent secondary vegetation (VS). Methods: Plots of 1 000 m² were used, 14 in yesales and 3 in VS. For soil sampling, we obtained a sample composed of each plot, and estimate pH, electrical conductivity (EC-salinity), % of calcium carbonates (CaCO3), organic matter (OM), phosphorus (P) and nitrogen content (N). The difference in species composition was estimated by similarity analysis (ANOSIM). We used rarefaction and extrapolation methods to standardize sample, and estimate diversity by Hill numbers (q = 0, q = 1 and q = 2). Linear regression was used to determine the relative influence of edaphic characteristics in diversity, average diameter, and height. Results: Soils in yesales presented low concentrations of OM, P, and N, with high values of EC-salinity and high percentages of CaCO3. In yesales, 6 443 individuals were recorded in 54 species and in the secondary vegetation 594 individuals and 62 species, the species composition being significantly different between both conditions. Diversity, average values of height, and diameter were significantly lower in yesales regarding the secondary vegetation, these differences were significantly related to edaphic conditions. Conclusions: Tree vegetation in yesales has a composition like the sub-evergreen forests of Calakmul. Small sizes in the arboreal individuals are related to the high percentage of CaCO3 and the high EC values, which partly condition the low availability of OM, N and P affecting the growth of the trees. This study supports the idea that precarious edaphic conditions have a negative influence on the diversity and horizontal and vertical structure of tree vegetation.